Longitudinal Links Between Media Use and Focused Attention Through Toddlerhood: A Cumulative Risk Approach - Gueron-Sela, Noa; Gordon-Hacker, Avigail (Frontiers in Psychology, 2020)
Previous studies that examined the links between media use and children’s attention abilities have yielded inconclusive findings. In the current study we aimed to move beyond the focus on isolated aspects of media use to a comprehensive assessment of both direct and indirect media use and practices in early childhood. Drawing from the cumulative risk literature, we examined whether cumulative media use is related to children’s subsequent attention abilities. Participants were 199 mothers of toddlers (60% male) who completed questionnaires assessing various aspects of children’s media use, as well as children’s focused attention abilities at three time points: 18 months (T1), 22 months (T2), and 26 months (T3) of age. Cumulative media use scores were computed based on four indicators: 1) child average daily screen time; 2) household background television; 3) maternal use of media to regulate child distress; and 4) maternal use of mobile devices while spending time with the child. An autoregressive cross-lagged path model controlling for child sex, maternal education and general parenting practices showed that cumulative media use at 18 months negatively predicted children’s focused attention at 22 months. Moreover, there was a significant negative indirect effect from cumulative media use at 18 months to focused attention at 26 months via focused attention at 22 months. Finally, the cumulative media index appeared to be a better predictor of focused attention than any of the singular media use indicators. Children’s focused attention did not predict subsequent cumulative media use across time, providing no evidence for bidirectional links. Findings suggest that exposure to multiple (rather than single) aspects of media use is related to decreased subsequent focused attention abilities during toddlerhood. Family media plans that designate media-free time and increase parental awareness to media use habits in the household should therefore be encouraged.